1992
DOI: 10.1227/00006123-199210000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Survival of Low-Grade Astrocytoma in Adults--1977–1988

Abstract: A retrospective review of the records of the Division of Neuropathology at the New York University Medical Center between 1977 and 1988 revealed 53 cases of adult supratentorial astrocytomas. Fifty were fibrillary, and three were gemistocytic. Two additional patients had pilocytic tumors and were not included in the study. The majority of patients had either a subtotal (64%) or gross total resection (19%). Biopsy (17%) was performed for deep-seated lesions and for those lesions confined to eloquent cortex. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(109 citation statements)
references
References 28 publications
4
97
1
7
Order By: Relevance
“…In some studies, patients with a lack of contrast enhancement have shown a prognostic benefit. 5,34 Because contrast enhancement was not at all significant in the survival analysis in this study (P-to-enter ϭ 0.82), and no interaction could be demonstrated between the variables in the Cox analysis, the prognostic value of the MET uptake cannot be explained by the association between PET and contrast enhancement.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In some studies, patients with a lack of contrast enhancement have shown a prognostic benefit. 5,34 Because contrast enhancement was not at all significant in the survival analysis in this study (P-to-enter ϭ 0.82), and no interaction could be demonstrated between the variables in the Cox analysis, the prognostic value of the MET uptake cannot be explained by the association between PET and contrast enhancement.…”
Section: Discussionmentioning
confidence: 61%
“…It has been assessed that 49 -85% of low-grade astrocytomas undergo transformation to a higher grade at some point along the course. [3][4][5] Malignant transformation occurs also in low-grade oligodendrogliomas. 6 Therefore, it is reasonable to assume that an early malignant transformation is responsible for the short survival in some of these patients.…”
mentioning
confidence: 99%
“…Thus, the prognostic relevance of tumor volume could be attributed either to the therapy is in accordance with the results of the current series (63% males). 3,7,18 or the biology of the tumor. In the current study the influence of treatment-related effects was minimized.…”
Section: Tumor Volumementioning
confidence: 99%
“…Havendo evidências de progressão da lesão, ou agravamento do estado neurológico, a exérese da lesão deve ser realizada. Idade inferior a 40 anos associase a prognóstico favorável 144 .…”
Section: Gliomas De Baixo Grauunclassified
“…Astrocitomas de tronco encefálico costumam apresentar prognóstico pior 183 . Influencia também a sobrevida dos doentes, a malignização das lesões 144 . Características radiológicas, histológicas e doses de radioterapia interferem na evolução, mas não foram avaliados durante a realização do presente estudo 183 .…”
Section: Gliomas De Baixo Grauunclassified